The Position of Corporate Testimony in the Criminal Law Evidence System for Corruption Crimes - Endy Sulistya Hudi Prayogo; Mohamad Tohari; Wieke Dewi Suryandari (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study discusses the position and validity of corporate testimony as evidence in the criminal procedural law in Indonesia, particularly in corruption crimes. Corporate testimony is becoming increasingly relevant in the context of the complex structures of modern organizations that are often involved in corrupt practices. Although recognized as legal subjects, challenges in using corporate testimony as evidence include difficulties in identifying responsible parties, decentralized decision-making, and confidentiality policies that hinder access to important documents. This study also analyzes the obstacles faced by law enforcement in proving corporate testimony and its implications for justice and accountability. It is hoped that through this study, solutions can be identified to enhance the efficacy of proving corporate testimony in legal enforcement against corruption crimes.